Relative frequency and estimated minimal frequency of Lysosomal Storage Diseases in Brazil: Report from a Reference Laboratory - Giugliani, Roberto (Genet Mol Biol, 2017)
Lysosomal storage diseases (LSDs) comprise a heterogeneous group of more than 50 genetic conditions of inborn errors of metabolism (IEM) caused by a defect in lysosomal function. Although there are screening tests for some of these conditions, diagnosis usually depends on specific enzyme assays, which are only available in a few laboratories around the world. A pioneer facility for the diagnosis of IEM and LSDs was established in the South of Brazil in 1982 and has served as a reference service since then. Over the past 34 years, samples from 72,797 patients were referred for investigation of IEM, and 3,211 were confirmed as having an LSD (4.41%, or 1 in 22), with 3,099 of these patients originating from Brazil. The rate of diagnosis has increased over time, in part due to the creation of diagnostic networks involving a large number of Brazilian services. These cases, referred from Brazilian regions, provide insight about the relative frequency of LSDs in the country. The large amount of data available allows for the estimation of the minimal frequency of specific LSDs in Brazil. The reported data could help to plan health care policies, as there are specific therapies available for most of the cases diagnosed.